Development of Temperature Monitoring System of Hospital Cold Storages Based on Wireless Network and its Database Management. - Seneviratne, Vindhya; Bae, Subin; Jeon, Seong Bin; Won, Yoochul; Yoon, Gilwon (Journal of Medical Systems, 2021)
Storing bio-specimens in adequate temperatures is an important task in hospitals. Usually an assigned employee records manually the temperatures of the hospital cold storages such as refrigerators and freezers that keep them at regular intervals. In this research, a low power wireless Bluetooth Low Energy network is applied where the central monitoring personal computer, receives the temperature data and stores in a database. The system consists of many beacons which are wirelessly sending the measured temperature data, and the central monitoring computer which allows the user to monitor that data. In the case of wireless signals getting blocked due to obstacles, repeaters called bridges send the data to the central computer forming a so-called scatter net. Once the data is received by the Bluetooth module connected to the monitoring computer, an application saves the data into a database. This web application forms a website where the users holding the authentication information can log in and monitor the temperature data in the form of tables and graphs. The same information can be viewed by a smartphone and a person in charge receives a warning SMS message. This system also provides a scheduled backup system where the database is automatically backed up periodically. The suggested system has the advantage of managing reagent records with reduced manpower whilst coping for emergency situations automatically.